Immune cells mediated the causal relationship between perturbational phenotyping of human blood cells and neuropathy pain: a two-sample and mediated mendelian randomized study: Immune mediation in blood cell phenotypes and neuropathic pain - Chen, Qingwen; Zhong, Tao; Liu, Jian; Cai, Dongpeng; Gao, Han; Chen, Mubin (Cellular and Molecular Biology, 2025)
Current research reveals a complex relationship between blood cells(BC) and neuropathic pain(NP), though the underlying biological mechanisms remain unclear. This study applies Mendelian randomization (MR) to investigate causal relationships between BC and three major types of NP: diabetic peripheral neuropathy(PDPN), postherpetic neuralgia(PHN), and trigeminal neuralgia(TN). We also explore the potential mediating role of immune cells in these associations. We employed a two-sample, two-step Mendelian randomization study using the inverse variance weighted method to investigate the causal effect of BC on three major types of NP, as well as the mediating role of immune cells in the association between BC and NP. Additionally, we utilized a two-step Mendelian randomization design to explore the mediating effect of immune cells. We identified 13 distinct blood cell phenotypes under various perturbation conditions that have a significant causal relationship with NP. Additionally, we discovered 127 immune cells that exhibit a notable causal connection with NP. Through Mendelian Randomization (MR) and two-step Mendelian Randomization analyses, we found the following results: Three blood cell phenotypes were associated with PDPN, three with PHN, and seven with TN, with platelet, red blood cell, monocyte, and neutrophil responses showing significant correlations with NP risks. Immune cell analyses revealed 36 phenotypes increasing and 31 decreasing PDPN risk, 16 increasing and 21 decreasing PHN risk, and 18 increasing and 13 decreasing TN risk, with HLA DR on DCs, PB/PC AC, and CD39+ CD4+ %T cell showing the strongest associations, respectively. Mediation analysis identified immune cells, such as CD39+ resting Treg and HLA DR+ CD4+ %lymphocyte, mediating PBC effects on NP risks. Sensitivity analyses confirmed no significant heterogeneity or pleiotropy, and reverse MR analyses found no reverse causal relationships. This study provides new evidence for the causal relationship between blood cell phenotypes and neuropathic pain and proposes immune factors with potential mediating effects. However, this finding needs to be further demonstrated by more extensive clinical studies.